Thymoquinone improves testicular damage and sperm quality in experimentally varicocele‐induced adolescent rats. (4th March 2021) - Gur, Fatih Mehmet; Timurkaan, Sema; Taskin, Eylem; Guven, Celal; Gur, Hatice Emel; Senturk, Meryem; Dastan, Sevgi; Nurdinov, Nursultan; Unalan, Adnan; Cankut, Senay; Tatyuz, Ilhan
Abstract: The aim of this study was to investigate the protective and therapeutic effects of thymoquinone against the negative effects of varicocele on testicular tissue and sperm morphology. Five groups were formed by random selection from a total of 40 adult male Wistar rats ( n  = 8). Thymoquinone (5 mg/kg/day) was administered intraperitoneally to the varicocele‐dimethyl sulfoxide‐olive oil‐thymoquinone (VT) group and the sham‐thymoquinone group. At the end of the 60th day, all groups were anaesthetised and the left testis was removed from the body quickly. One half of the testis tissue, which was divided into two, was separated for biochemical and Western blot analysis, while the other half were fixed in Bouin's fixative. As a result of biochemical, molecular and histopathological analyses, a statistically significant increase was found in the varicocele group testicular tissues in the malondialdehyde level, apoptotic index, Bax expression, cytochrome c expression and Bax/Bcl‐2 ratio compared with the sham group. In addition, histopathological changes characterised by partial or complete degeneration of the germinal epithelium were observed in the seminiferous tubules in the same group. Total oxidant status level and sperm count with abnormal morphology increased in varicocele group, whereas total antioxidant status level decreased. In the VT group, all of the biochemical, molecular and histopathological changes detected in the varicocele group were statistically significantly reduced. When the findings obtained in this study are evaluated, it can be said that thymoquinone has the potential to be used as a preventive and therapeutic pharmacological agent in the medical treatment of varicocele. Although the exact mechanism of action of thymoquinone has not been fully elucidated, the findings obtained in this study support the view that thymoquinone showed a cytoprotective effect by reducing apoptosis, oxidative stress and lipid peroxidation.